Comprehensive Analysis of the Carcinogenic Process, Tumor Microenvironment, and Drug Response in HPV-Positive Cancers - Yu, Xiaorong; Xu, Jiankai; Xu, Dahua; Bi, Xiaoman; Wang, Hong; Lu, Yanda; Cao, Meng; Wang, Wenxiang; Xu, Zhizhou; Zheng, Dehua; Chen, Liyang; Zhang, Xiaodian; et al. (Frontiers in Oncology, 2022)
Human papillomavirus (HPV) is a common virus, and about 5% of all cancers worldwide are caused by persistent high-risk HPV infections. Here, we reported a comprehensive analysis of the molecular features for HPV-related cancer types using TCGA (The Cancer Genome Atlas) data with HPV status. We found that the HPV-positive cancer patients had unique oncogenic process, tumor microenvironment and drug response compared with HPV-negative patients. In addition, HPV improved overall survival for the four cancer types, including cervical squamous cell carcinoma (CESC), head and neck squamous cell carcinoma (HNSC), stomach adenocarcinoma (STAD), and uterine corpus endometrial carcinoma (UCEC). The stronger activity of cell cycle pathways and lower driver gene mutation rates were observed in HPV-positive patients, which implied the different carcinogenic process between HPV-positive and HPV-negative groups. The increased activities of immune cells and differences in metabolic pathways helped explain the heterogeneity of prognosis between the two groups. Furthermore, we constructed HPV prediction models for different cancers by virus infection score (VIS) which was linearly correlated with HPV load, and found that VIS was associated with drug response. Altogether, our study reveals HPV-positive cancer patients have unique molecular characteristics which help the development of precision medicine in HPV-positive cancers.